The Choice of Legal Basis for Acts of the European Union Competence Overlaps, Institutional Preferences, and Legal Basis Litigation - Engel, Annegret (Springer International Publishing, 2018)
This book provides the first comprehensive discussion of conflicts between legal bases in EU law. It fills an important gap in the existing literature on the choice of legal basis in EU law by analysing the structure of legal bases and the resulting legal basis litigation in the European Union, thus identifying areas of conflict produced by overlapping competences, divergent inter-institutional interests, and inconsistencies in the courts' judgements. While certain cases have been discussed extensively in academic literature (e.g. Tobacco Advertising, ECOWAS), there has been little analysis of the general underlying criteria and principles governing the choice of legal basis on the part of European institutions. Such an analysis has, however, become necessary in order to better understand and possibly predict judicial outcomes, and to identify flaws in the current legislative framework.